(untitled) - Schofield, Phil (Louisville, 1989)
Established in 1908 in Edmonton, the capital of Alberta, the University of Alberta is a public research university in Canada, located at the edge of the North Saskatchewan River valley. Its main campus spans about 50 blocks of the city, and the university comprises a total of 150 buildings spread over four campuses. Edmonton is home to the world’s second biggest fringe theatre festival, a folk music festival, and the university’s ‘festival of ideas’. Its South Campus focuses on agricultural research and is also home to a 32,516m2 sports centre, which incorporates various sports clubs, 14 varsity teams and the Canadian women’s national basketball team. In keeping with Edmonton’s French-speaking community, the university offers French instruction at the Faculté Saint-Jean, which provides courses in arts, science, education, commerce, engineering, nursing, conservation and environmental sciences.
Keywords: Đại học Alberta,University of Alberta; Lịch sử,History